Sintering behavior and electrochemical performances of nano-sized gadolinium-doped ceria via ammonium carbonate assisted co-precipitation for solid oxide fuel cells - Joh, Dong Woo; Rath, Manasa K.; Park, Jin Wan; Park, Jeong Hwa; Cho, Ki Hyun; Lee, Seunghwan; Yoon, Kyung Joong; Lee, Jong-Ho; Lee, Kang Taek (ELSEVIER SCIENCE SA, 2016)
Ultra-fine Gd-doped ceria (GDC) powders were synthesized via co-precipitation using ammonium carbonate as the precipitant. The crystallite size of the resultant GDC powders was measured as similar to 33 nm. The dilatometry test of the powder compacts and the relative density measurement of sintered pellets with various sintering temperatures revealed the synthesized nano-GDC powders had superior sinterability compared to commercial GDC powders (e.g., 96% vs 78% in relative density at 1300 degrees C, respectively). Based on the total conductivity measurement of the co-precipitated GDC via electrochemical impedance spectroscopy, we found there was an optimum sintering temperature range (1300-1400 degrees C) to achieve both high density and high conductivity due to significant increase in grain boundary resistance at higher temperature (1500 degrees C). Moreover, the nano-sized and highly sinterable co-precipitated GDC effectively enhanced oxygen reduction reaction at the La0.6Sr0.4Co0.2Fe0.8O3-delta/GDC composite cathode due to increase in active reaction sites as well as enhanced phase connectivity in 3D-bulk at lower sintering temperatures. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: ELECTRICAL-PROPERTIES; CONDUCTIVITY; TEMPERATURE; ELECTROLYTES; FABRICATION